LITIGATION AND LEGITIMACY IN ENVIRONMENTAL ACTIONS IN THE LIGHT OF INFRACONSTITUTIONAL LEGISLATION: THE CHALLENGE OF ACCESS TO ENVIRONMENTAL JUSTICE - Medeiros Pirangy de Souza, Karina; Zoim da Silva, Edilene; Souza da Silva, Levy; Eduarda de Souza Rodrigues, Maria; Reis Costa, Rayandra; Pirangy de Souza, Alexandre; Pires Fonseca, Marcello (Revista Gênero e Interdisciplinaridade, 2023)
Environmental actions often involve conflicts of interest between companies that seek to maximize their profits and local communities that seek to protect their environment and quality of life, with an explicit asymmetric relationship between those involved, both due to the population’s lack of knowledge and the influence of large corporations. The purpose of this summary is to analyze the legitimacy of filing environmental actions in the light of infraconstitutional legislation in order to ascertain the accessibility of filing demands to the population. To this end, an analytical study will be presented, presenting the main characteristics regarding the proposition of environmental demands, in order to demonstrate the possibilities brought by the legislation. In addition, a document analysis of laws, rules and regulations related to the filing of individual and collective claims was carried out. In view of the results obtained, it is concluded that despite the legislator’s intention to provide the individual with the possibility of litigating individually or collectively, this is hampered by the population’s lack of information and the lack of resources to pay for the progress of processes of this magnitude.